Penguatan kemandirian kesehatan masyarakat melalui edukasi dan budidaya tanaman obat keluarga (toga) oleh Kkm 61 Catalyst UIN Malang di desa Sumberpetung - Syahrani, Olivia (Maliki Interdisciplinary Journal, 2026)
Family Medicinal Plants (TOGA) represent a promotive and preventive strategy in strengthening community health independence based on local resources. However, the utilization of TOGA at the household level has declined due to limited herbal health literacy and insufficient cultivation skills. Sumberpetung Village, Kalipare District, Malang Regency, possesses yard land potential that has not been optimally utilized for medicinal plant development. The community service program conducted by KKM 61 Catalyst UIN Maulana Malik Ibrahim Malang implemented an integrated approach consisting of educational sessions on herbal benefits, cultivation training, establishment of a TOGA demonstration garden, and training on processing herbal products into value-added goods. The program was conducted from January to February 2026 and involved 48 active participants. Pre-test and post-test evaluations indicated a 62% average increase in participants’ understanding of TOGA benefits and cultivation techniques. Furthermore, 71% of participants began planting at least three types of medicinal plants in their home yards after the training. The results demonstrate that integrating conceptual education with practical activities effectively enhances health literacy, cultivation skills, and local herbal-based economic opportunities. The program contributes to strengthening sustainable community health independence at the village level.